Strain-concentration factor of internally pressurized thick-walled cylinders - Tlilan, Hitham M.; Jawarneh, Ali; Ababneh, Amer Khalil; Tarawneh, Mohammad; Rababah, Mahmoud; Smadi, Othman (Zielona Góra: Uniwersytet Zielonogórski)
This study introduces a new definition of the strain-concentration factor (SNCF) of thick walled internally pressurized cylinders. The stress state has been considered in this new definition; i.e. triaxial and biaxial stress states for closed and open ends, respectively. Primarily, the curvature effect of the strain concentration has been studied here. To this end, the inner radius of the employed cylinders has been changed from 0.5 to 50.8 mm. On the other hand, the thickness has been kept constant at 16.7 mm.
Keywords: vessels; stress; strain; strain concentration